The Geophysical Risk Matrix: An Innovative Risk Analysis Tools for Earth-Rock Dam Failures Inspection - Poomvises N.; Pakdeerod P.; Kongsuk A.; Sintuboon N.; Sawasdipong B.; Husain M.K.; Harith Z.Z. (Springer, 2023)
To inspect old earthen dam of Royal Irrigation Department, Thailand, geophysical investigation is selected as non-destructive method. Three geophysical techniques, resistivity imaging, shear wave (MASW) survey, and ground penetrating radar are integrated to form a process innovation of dam inspection using geophysics. A five-year research was carried out and testing on twenty dam sites exhibiting the process innovation. In this account, three geophysical criteria of sub processes and an index of dam condition were initiated. Among those, the overlapping of anomalies plotted on risk matrix of dam play important role in the evaluating stage. The innovation is currently be applied to several old dams in responsible of the Royal Irrigation Department. 2020, Springer Nature Singapore Pte Ltd.